(untitled) (Zaporizhzhia Historical Review, 2021)
In this article the attempt to investigate a functioning of State machinery of commissioners on business of the Russian Orthodox Church at the Council of Ministers of USSR realized. The analysis of quality of their cadre, the degree of material security and attitude to them from the direction of soviet and party functionaries is given. Establishing the features of status commissioners in the regional executive committees of workers.